Políticas públicas/estatais e Programa Nacional de Educação na Reforma Agrária : estudo dos efeitos do PRONERA no sudoeste baiano - Costa, Sidiney Alves (Universidade Federal de São Carlos, 2017)
Based on the assumption that the objective conditions of capitalist society delimit the possibilities of State-Society-Social Movements relationship and mark the public/state policy to meet focused demands and ensure the social cohesion of the capitalist mode of production, the thesis studies the National Program of Education in Agrarian Reform (PRONERA), created in 1998 to answer literacy demands and to increase the schooling of Agrarian Reform settlers. Its central objective was to analyze the educational formation inside the PRONERA, problematizing the effects that it has for the education of the settlers. In order to do so, it chose as object of study the execution of PRONERA in the Southwest Region of Bahia, from 1998 to 2015, analyzing the projects of Literacy, Elementary Education and Technical Education of Medium Level realized by the State University of the Southwest of Bahia (UESB), in agreement with INCRA / PRONERA, to identify their effects on the access of the settlers to the superior courses offered by the State University of Bahia (UNEB), executed in agreement with INCRA / PRONERA. The documents show that PRONERA increases the schooling of beneficiaries who did not attend the regular educational system. However, because it is a Program that implements projects, with defined objectives and time, subject to the conjuncture of the university, government agencies and the political and economic situation of the country, it doesn‘t allow the majority of the settlers access to the projects, even more to the higher level, resulting in a public/state policy that serves both to focus interests and to ensure social cohesion.
Keywords: Estado; Políticas públicas; Educação; Movimentos sociais e educação; State; Public policies; Social movements and education; CIENCIAS HUMANAS::EDUCACAO